Sejarah dan Dinamika Pendidikan Katolik: Studi pada Yayasan Insan Mandiri di Singaraja Sebagai Sumber Belajar Sejarah - Linda Zal Medes Mendrofa; Tuty Maryati; I Made Pageh (Universitas Veteran Bangun Nusantara, 2026)
This study examines the historical development and educational dynamics of the Insan Mandiri Foundation in Singaraja as one of the Catholic educational institutions that has contributed to the social and educational landscape of the region since the 1960s. Rooted in the social reality of multicultural life in Singaraja, this research aims to describe the history of the establishment of the Insan Mandiri Foundation, analyze its institutional dynamics, and explore its potential as a resource for history learning. The study employs a historical research method with a qualitative approach, including heuristics through observation, interviews, and document analysis, followed by source criticism, interpretation, and historiography. The findings reveal that Catholic education under the auspices of the Insan Mandiri Foundation has undergone continuous development since its establishment in 1961 while maintaining its religious identity amid changing social conditions. The dynamics of the foundation are reflected in institutional transformation, changes in the names of educational units, and the strengthening of its social role in education. Furthermore, this study shows that the historical experiences and institutional dynamics of the foundation can be integrated into contextual and locally-based history learning. The values embedded in its historical development represent multiculturalism, educational transformation, and social adaptation that are relevant to students’ understanding of local history